Plasma homocysteine and MTHFRC677T polymorphism as risk factors for incident dementia - Ford, A.; Flicker, L.; Alfonso, Helman; Hankey, G.; Norman, P.; Van Bockxmeer, F.; Almeida, O. (2012)
Background: Elevated total plasma homocysteine (tHcy) has been associated with increased risk of dementia. The C677T polymorphism of the 5,10-methylenetetrahydrofolate reductase gene (MTHFR) increases tHcy and provides a means of studying the association between tHcy and dementia while not being as susceptible to the common biases and confounding of observational studies. The authors designed this longitudinal study to determine if high tHcy and the MTHFR C677T polymorphism increase the risk of incident dementia among older men. Methods: The authors studied 4227 men aged 70-89 years from the Health in Men Study cohort and established the diagnosis of dementia (International Classification of Diseases - 10th edition) using morbidity and mortality records. Information on tHcy, MTHFR gene status, lifestyle and clinical variables were obtained using postal and face-to-face assessments. Results: 230 men (5.4%) developed dementia during the mean follow-up period of 5.8±1.6 years (range 0.1-8.2 years). The hazard of dementia increased with a doubling of tHcy concentration (adjusted HR 1.48, 95% CI 1.10 to 2.00) and was higher in men with tHcy >15 µmol/l (adjusted HR 1.36 95% CI 1.03 to 1.81, p=0.032). Men with the TT genotype had a HR of dementia of 1.25 (95% CI 0.81 to 1.92). Conclusions: The results of this prospective study are consistent with a causal link between high tHcy and incident dementia, but the study lacked power to determine an effect of the MTHFR genotype.